2004
DOI: 10.1038/sj.npp.1300478
|View full text |Cite
|
Sign up to set email alerts
|

Increased Fear Learning Coincides with Neuronal Dysinhibition and Facilitated LTP in the Basolateral Amygdala following Benzodiazepine Withdrawal in Rats

Abstract: Animals chronically administered with diazepam (DZM -2 mg/kg/day i.p.) or vehicle (VEH) for 21 days were tested in a fear-conditioning paradigm 4 days after the last administration. Increased freezing was observed in DZM withdrawn rats as compared to VEH injected control rats in both associative and nonassociative context and this increase was greatest for the DZM withdrawal group in the paired context. In animals anesthetized with urethane, single pulses in the medial prefrontal cortex evoked a field potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 89 publications
10
32
0
Order By: Relevance
“…A recent study screening for autism-like symptoms in children with mood and anxiety disorders also found that up to 62% of these children fall into the autistic spectrum and might qualify for a possible diagnosis of autism (Towbin et al, 2005). Thus, we would like to speculate that enhanced amygdaloid processing in the basolateral complex, possibly due to a failure in inhibition, may account for enhanced fears (Isoardi et al, 2004;Rodriguez Manzanares et al, 2005) and lead to a reduction in social interactions. This is supported by a rodent study showing that lesioning the BLA, the main relay station for fear associations, impaired not only fear conditioningFa well established finding (LeDoux et al, 1990)Fbut also led to an increase, rather than a decrease, in social interactions (Woolley et al, 2006).…”
Section: Indirect Effects Of Non-amygdala Regionsmentioning
confidence: 88%
See 1 more Smart Citation
“…A recent study screening for autism-like symptoms in children with mood and anxiety disorders also found that up to 62% of these children fall into the autistic spectrum and might qualify for a possible diagnosis of autism (Towbin et al, 2005). Thus, we would like to speculate that enhanced amygdaloid processing in the basolateral complex, possibly due to a failure in inhibition, may account for enhanced fears (Isoardi et al, 2004;Rodriguez Manzanares et al, 2005) and lead to a reduction in social interactions. This is supported by a rodent study showing that lesioning the BLA, the main relay station for fear associations, impaired not only fear conditioningFa well established finding (LeDoux et al, 1990)Fbut also led to an increase, rather than a decrease, in social interactions (Woolley et al, 2006).…”
Section: Indirect Effects Of Non-amygdala Regionsmentioning
confidence: 88%
“…In fact, amygdalar disinhibition induced either by GABAergic blockade (Isoardi et al, 2004), genetic knockout of the GABA B(1a) -receptor subtype (Shaban et al, 2006), benzodiazepine withdrawal (Isoardi et al, 2004), dopamine receptor activation (Bissiere et al, 2003), or stress (Rodriguez Manzanares et al, 2005), can result in amygdaloid hyperexcitability (Isoardi et al, 2004;Rodriguez Manzanares et al, 2005) and facilitate LTP induction (Bissiere et al, 2003;Rodriguez Manzanares et al, 2005;Shaban et al, 2006), which have been associated not only with enhanced fear memories (Isoardi et al, 2004;Rodriguez Manzanares et al, 2005), but also with overgeneralization of conditioned fear to neutral stimuli (Shaban et al, 2006). These reports suggest that the hyperreactivity and hyperplasticity observed in this study may be due to a deficit in inhibition in the amygdala.…”
Section: A Novel Role Suggested For the Amygdala In Autismmentioning
confidence: 99%
“…For the stronger conditioning procedure (Experiment 4), animals were placed in the conditioning chamber, allowing a 3-min acclimation period followed by three footshocks (0.5 mA, 3-sec duration at an intershock interval of 30 sec). Animals remained in the chamber for an additional 2 min (post-shock period), after which rats were removed and subsequently placed in their home cages (Isoardi et al 2004;Rodriguez Manzanares et al 2005;Bustos et al 2006).…”
Section: Contextual Fear Conditioningmentioning
confidence: 99%
“…The conditioning procedure used was similar to the one previously described (Isoardi et al, 2004;Bustos et al, 2006). Rats were habituated to handling and injected with SAL for at least 2 days prior to the start of each experiment.…”
Section: Behavioral Proceduresmentioning
confidence: 99%